2014
DOI: 10.1038/ki.2013.503
|View full text |Cite
|
Sign up to set email alerts
|

Nlrp3 is a key modulator of diet-induced nephropathy and renal cholesterol accumulation

Abstract: Metabolic syndrome (MetSyn) is a major health concern and associates with the development of kidney disease. The mechanisms linking MetSyn to renal disease have not been fully elucidated but are known to involve hyperuricemia, inflammation, and fibrosis. Since the innate immune receptor Nlrp3 is an important mediator of obesity and inflammation, we sought to determine whether Nlrp3 is involved in the development of MetSyn-associated nephropathy by giving wild-type or Nlrp3-knockout mice a Western-style compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 65 publications
3
66
0
Order By: Relevance
“…SREBP1 hyperactivity and NLPR3 inflammasome activation in lesions are detected in atherosclerotic pig aortas with vascular inflammation (23). Studies by us and others showed that fructose induced NLRP3-dependent renal inflammation and steatosisassociated metabolic syndrome (1,14). In this study, inhibition of NLRP3 expression and caspase-1 activity reverted fructose-induced transcriptomic dysregulation of PPAR-a, SREBP1, and SCD1 in hepatocytes, suggesting that NLRP3 inflammasome activation plays a role in fructose-induced aberrations in hepatocellular lipid metabolism.…”
Section: Figmentioning
confidence: 53%
“…SREBP1 hyperactivity and NLPR3 inflammasome activation in lesions are detected in atherosclerotic pig aortas with vascular inflammation (23). Studies by us and others showed that fructose induced NLRP3-dependent renal inflammation and steatosisassociated metabolic syndrome (1,14). In this study, inhibition of NLRP3 expression and caspase-1 activity reverted fructose-induced transcriptomic dysregulation of PPAR-a, SREBP1, and SCD1 in hepatocytes, suggesting that NLRP3 inflammasome activation plays a role in fructose-induced aberrations in hepatocellular lipid metabolism.…”
Section: Figmentioning
confidence: 53%
“…These results are consistent with other reports showing noncanonical effects of Nlrp3 in the kidney. 15,16,27,29 Next to cytokines, renal function is influenced by tubular damage and repair. Interestingly, we observed that renal apoptosis was reduced in mice lacking Nlrp3 expression in leukocytes, suggesting that leukocyte-associated Nlrp3 influences tubular epithelial apoptosis and, thereby, renal dysfunction.…”
Section: Nlrp3 Regulates Renal Repairmentioning
confidence: 99%
“…The activation of NLRP3 inflammasome finally triggers the maturation of IL-1␤ and IL-18 via activated caspase-1. Growing evidence indicates that the NLRP3 inflammasome is associated with the progression of kidney diseases (12)(13)(14). Recently, several reports have further demonstrated that activation of inflammasome can be regulated by a mitochondrial mechanism (8,15,16).…”
mentioning
confidence: 99%